Análise comparativa do perfil de segurança e eficácia analgésica da S(+) cetamina com ou sem morfina na anestesia peridural para histerectomia abdominal - Castillo, Daniela Lima Chow (2009)
The association of drugs with different mechanisms of action in the dorsal horn of the spinal cord decreases postoperative pain, with a reduction in the incidence of side effects. The aim of this study was to evaluate some intraoperative parameters as well as postoperative analgesia and sedation by epidural morphine, S(+)ketamine and S(+) ketamine- morphine associated with Bupivacaine Enantiomeric Mixture (R75L25%) for abdominal hysterectomy. In this prospective, randomized, and double-blinded clinical trial, the efficacy and safety of the administration of epidural S(+)ketamine alone or with morphine were compared with epidural morphine alone (control group) for efficacy and safety comparisons after abdominal hysterectomy. 36 female patients, physical status ASA I and II, participated in this study. These patients were randomly allocated to one of the three treatment groups for having the following drugs administered epidurally: 1. Ketamine Group - Bupivacaine Enantiomeric Mixture (R75L25%) associated with S(+) ketamine (0.4 mg.kg-1); 2. Ketamine-Morphine Group - Bupivacaine Enantiomeric Mixture (R75L25%) associated S(+) ketamine (0.4 mg.kg-1) and morphine (1 mg) 3. Morphine Group, Bupivacaine Enantiomeric Mixture (R75L25%) was associated with morphine (2mg). During the intraoperative period the parameters analyzed were: blood pressure, heart rate, motor blockade level, sensitive level, intraoperative use of vasoconstrictor and sedation level. The time interval between each dada collection was 15 minutes. In the postoperative period, analgesia were evaluated using analogue visual scale 2h, 6h and 24h after the end of the surgery as well as the total amount of analgesics drugs requirement during the first 24 postoperative hours. Values were analyzed statistically using GraphPad Prisma 4.0 and Excel 2007. There were no differences between the three groups with respect to age, sex, weight, or duration of the surgical procedures (p<0,05). No differences were found between the groups during intraoperative analysis related to blood pressure, heart rate, Ramsay scores, vasoconstrictor use, and sensitive blockade level. Bromage’s scores were lower in the morpine/s+ketamine group during the first fifteen minutes analysis. Sedation scores were similar in both groups. The epidural blockade alone was not enough for surgical anesthesia resulting in conversion to general anesthesia in 4 patients who belong to Ketamine-morphine (02 patients) and Morphine (02 patients) groups, respectively. None of the patients in either group developed respiratory depression. Other side effects, such as pruritus, nausea, and vomiting, were also similar in both groups. The addiction of s(+) ketamine was safety and efficient to Bupivacaine Enantiomeric Mixture (R75L25%) in comparison with morphine.